On a class of non-linear differential equations with exact solution - Bich, Dao Huy; Bich, Nguyen Dang (Vietnam Journal of Mechanics, 2012)
The present paper deals with a class of non-linear ordinary second-order differential equations with exact solutions. A procedure for finding the general exact solution based on a known particular one is derived. For illustration solutions of some non-linear equations occurred in many problems of solid mechanics are considered.